Internalization of Character Education from the Perspective of Ibn Qayyim al-Jawziyyah in the Post-Truth Era: Internalisasi Pendidikan Karakter Perspektif Ibnu Qayyim al-Jauziyyah di Era Post-Truth - Kusuma, Hanif Indra; Naya, Arsya; Az-Zahra, Adinda Najwa; Pragita, Ayunda Sherin; Syahbani, Salsa Nurfarida Nisfa Syahri (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2026)
Value disorientation has become a significant challenge faced by the education system due to rapid technological advancement, resulting in a loss of clear value orientation. In the post-truth era, truth is often perceived as relative, leading to the formation of public opinions that influence societal perspectives. The concept of character education proposed by Ibn Qayyim al-Jawziyyah can serve as a foundation for maintaining ethical and moral values in the post-truth era. His concept of furūsiyyah emphasizes the balance between the soul, body, and morality as the basis for character formation. This study employs a library research method with a descriptive-analytical approach. The objective of this research is to examine the concept of furūsiyyah according to Ibn Qayyim al-Jawziyyah as an ethical and moral foundation to address value disorientation in the post-truth era. The findings indicate that Ibn Qayyim al-Jawziyyah’s concept of character education offers a relevant solution to the current value crisis. Through the concept of furūsiyyah, education is directed toward developing individuals with a balanced integration of spiritual, physical, and moral aspects, thereby fostering strong and integrated character. (Disorientasi nilai menjadi tantangan yang dihadapi oleh sistem pendidikan akibat pesatnya kemajuan teknologi, sehingga orientasi nilai tidak lagi memberikan arah yang tepat. Di era post-truth, kebenaran sering kali dianggap relatif, sehingga memicu terbentuknya opini publik yang memengaruhi cara pandang masyarakat. Konsep pendidikan karakter menurut Ibnu Qayyim al-Jauziyyah dapat dijadikan sebagai landasan untuk mempertahankan nilai-nilai etika dan moral di era post-truth. Konsep furūsiyyah yang ditawarkannya menekankan keseimbangan antara jiwa, raga, dan moral sebagai fondasi pembentukan karakter. Metode penelitian yang digunakan adalah studi pustaka (library research) dengan pendekatan deskriptif-analitis. Penelitian ini bertujuan untuk mengkaji konsep furūsiyyah menurut Ibnu Qayyim al-Jauziyyah sebagai landasan etika dan moral dalam mengatasi disorientasi nilai di era post-truth. Hasil kajian menunjukkan bahwa konsep pendidikan karakter menurut Ibnu Qayyim al-Jauziyyah mampu menjadi solusi dalam menghadapi krisis nilai. Melalui konsep furūsiyyah, pendidikan diarahkan untuk membentuk individu yang memiliki keseimbangan antara aspek spiritual, fisik, dan moral, sehingga melahirkan karakter yang kuat dan berintegritas.)